Design, synthesis and protein-targeting properties of thioether-linked hydrogen bond surrogate helices - Mahon, Andrew B. (2011)
Appropriately-placed hydrogen bond surrogates have been demonstrated to efficiently nucleate helical conformations. Herein we describe an efficient method for the synthesis of thioether-based hydrogen bond surrogate (teHBS) helices. A teHBS helix is shown to adopt a stable conformation and target its cognate protein receptor with high affinity.